TECHNICAL AND ECONOMIC RATIONALE FOR THE USE OF TURBULA TYPE MACHINING MACHINES IN POLISHING THE SURFACE OF SMALL POLYMER POLYMERS - ZALYUBOVSKYI, Mark (Herald of Khmelnytskyi National University. Technical sciences, 2022)
A method of wet polishing of polymer parts using a galvanizing machine with a complex spatial movement of the working tank type «Turbula» is proposed. According to the proposed method, the main stage of polishing the surface of the parts is carried out by abrasive ceramic bodies of complex geometric shape with the addition of fine pumice in the implementation of mixed cascade-waterfall mode of movement of the bulk working medium. This method of processing parts is considered highly productive, the processing time of parts averages 15 hours of continuous operation of the machine, which is several times faster than when processing parts in rotating drum drums or vibrating machines. The latter are characterized by low productivity of the relevant technological operations. The feasibility study of the method of wet polishing of polymer parts using a galvanizing machine with a complex spatial movement of the working capacity of the «Turbula» type for the implementation of the technological operation of polishing the surface of polyester buttons was performed analytically. The expected annual economic effect from the implementation of the developed method of wet polishing of polymer parts using a galvanizing machine with a complex spatial movement of the working capacity of the «Turbula» type, which will amount to UAH 14,059.8 per two units of equipment, is calculated. This method of processing can be used to improve the surface quality of any polymer parts with the possibility of achieving the appropriate value of the roughness of their surface. The obtained research results can be used in design bureaus of relevant enterprises for the manufacture of small polymer parts, the surface quality of which is determined by organoleptic method, as well as in design bureaus of machine-building enterprises specializing in the development of galvanizing equipment.